Integrated and participatory nutrition and food safety risk assessment for wet markets - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
This has been successfully applied in a research context but not yet institutionalised by national food systems. A tool kit has been developed and several papers published but methods are not being used more widely. A special issue of Global Food Security featured several applications of the framework.